Altered Skin Permeation of Finasteride Using Clove Oil, Urea, and Lyophilized Powder of Grape Seed Extract - Anayatollah Salimi; Hamid Mohammad Soleymani; Saeed Mohammad Soleymani (Tabriz University of Medical Sciences, 2023)
Purpose: Finasteride is a 5-alpha reductase inhibitor used to treat hair loss and acne. The skin permeation of finasteride is one of the main challenges associated with dermal drug delivery. One way to overcome the skin barrier is to use penetration enhancers. The purpose of this study was to investigate the effect of some penetration enhancers on finasteride permeability on the skin, as well as the effect of pretreatment time on their efficacy. Methods: In order to determine the effect of penetration enhancers on the skin permeability of finasteride, the skin was exposed to clove oil, urea, and lyophilized powder of grape seed extract (LPGSE) at different pretreatment times (2, 4 h), and then the permeability parameters were determined by passing the drug through the skin. Results: The results of this study showed that clove oil, urea, and LPGSE increased the transfer of finasteride from the skin. The highest rate of permeation was observed with clove oil (4 h), and the least permeability was observed with urea (4 h). Conclusion: Increasing the pretreatment time with clove oil and LPGSE increases the permeability of finasteride. Meanwhile, the increase in pretreatment time with urea reduces the penetration of finasteride from the skin due to reversible effects.